Kill and tell - Howard, Linda, 1950- (Pocket Star Books, 2003)
Targeted for murder after she takes custody of a mysterious notebook, Karen Whitlaw is protected by detective Marc Chastain, with whom she begins a passionate relationship while they seek to uncover the mystery behind the notebook's past.